2013
DOI: 10.1002/eat.22196
|View full text |Cite
|
Sign up to set email alerts
|

Are improvements in shame and self‐compassion early in eating disorders treatment associated with better patient outcomes?

Abstract: Compassion-focused therapy (CFT; Gilbert, 2005, 2009) is a transdiagnostic treatment approach focused on building self-compassion and reducing shame. It is based on the theory that feelings of shame contribute to the maintenance of psychopathology, whereas self-compassion contributes to the alleviation of shame and psychopathology. We sought to test this theory in a transdiagnostic sample of eating disorder patients by examining whether larger improvements in shame and self-compassion early in treatment would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 44 publications
5
90
1
5
Order By: Relevance
“…Baseline self-compassion and fear of self-compassion interacted to predict changes in eating disorder symptoms over time for individuals being treated in specialised eating disorder programs. 33 Specifically, poorer outcomes we observed for patients who were both fearful of, and low in, self-compassion, for example, patients who were low in self-compassion only experienced a poor outcome if they were also fearful of selfcompassion, and vice versa. For individuals with BED, greater concerns about shape and weight were predictive of non-response at the end of treatment among those patients with low interpersonal problems.…”
Section: Interactive Simple Predictors Of Treatment Outcomementioning
confidence: 88%
See 1 more Smart Citation
“…Baseline self-compassion and fear of self-compassion interacted to predict changes in eating disorder symptoms over time for individuals being treated in specialised eating disorder programs. 33 Specifically, poorer outcomes we observed for patients who were both fearful of, and low in, self-compassion, for example, patients who were low in self-compassion only experienced a poor outcome if they were also fearful of selfcompassion, and vice versa. For individuals with BED, greater concerns about shape and weight were predictive of non-response at the end of treatment among those patients with low interpersonal problems.…”
Section: Interactive Simple Predictors Of Treatment Outcomementioning
confidence: 88%
“…In adults with either AN or BN, a greater reduction in shame (in regards to their body, character, and behavior) during the first 4 weeks of treatment lead to faster rate of improvement in eating disorder symptoms over 12 weeks of treatment (r 5 0.23). 33 In the same study, an early increase in self-compassion led to greater reductions in shame over 12 weeks (r 5 0.15). A novel mediational finding in a recent study suggested that changes in parent self-efficacy during the course of family based treatment predicted adolescents' treatment outcome in a sample of 49 adolescents with AN or BN.…”
Section: Mediatorsmentioning
confidence: 88%
“…Importantly, participants' mean estimated self-compassion scores before the intervention were within one standard deviation (SD) of eating disorder patient samples (Kelly et al, 2014) but following the intervention were within one SD of female community samples (Neff, 2003a). The 2-week self-compassionate letter-writing intervention appeared to be acceptable, feasible, and efficacious.…”
Section: Discussionmentioning
confidence: 91%
“…Given the dangers of the disorder, it is critical to developing alternate interventions that may be more acceptable to these individuals, which could in turn foster greater motivation for specialized treatment. There is now evidence in transdiagnostic samples of individuals with eating disorders that developing self-compassion can lead to a reduction in shame and eating pathology (Gale, Gilbert, Read, & Goss, 2014;Kelly, Carter, & Borairi, 2014). There is now evidence in transdiagnostic samples of individuals with eating disorders that developing self-compassion can lead to a reduction in shame and eating pathology (Gale, Gilbert, Read, & Goss, 2014;Kelly, Carter, & Borairi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another series of studies-towards selfcompassion and eating disorders-have shown that (1) a larger improvement of selfcompassion early in treatment was related to a larger decrease of feelings of shame, and that a larger decrease of shame early in treatment was related to a faster decrease of eating disorder symptoms in a transdiagnostic sample (Kelly, Carter, & Borairi, 2014), (2) a compassion-focused self-help intervention for inpatients with a binge eating disorder was more effective in ameliorated eating disorder symptoms, weight concern and selfcompassion compared to a CBT-based self-help intervention (Kelly & Carter, 2015) and (3) a compassion-focused therapy group added to care as usual was more effective than solely care as usual on self-compassion, shame and eating disorder symptoms in a transdiagnostic outpatient sample (Kelly, Wisniewski, Martin-Wagar, & Hoffman, 2016).…”
Section: Implementation In Practicementioning
confidence: 99%